Analysis of Students’ Mathematical Communication Ability Based on Self-Regulated Learning - Yunita Dalimunthe; Siti Zubaidah Dalimunthe; Isra Suna Hasibuan (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
This research is motivated by previous researchers and the facts in the field that students’ mathematical communication skills have not been trained properly, and there are various levels of difficulty experienced by students in learning mathematics, while the influencing factor is one of the affective aspects, namely self-regulated learning. This study aims to describe students’ mathematical communication skills in terms of self-regulated learning. The subjects of this study were 60 students of MAN Simalungun class X. The method used in this study is a descriptive method with a quantitative approach. The instrument in this study is a written test of mathematical communication skills and a non-test in the form of a self-regulated learning questionnaire. The results showed that: 1) there were significant differences in mathematical communication skills between students with low, medium, and high self-regulated learning categories; 2) there are significant differences in students’ mathematical communication skills in terms of the dimensions of self-regulated learning, namely motivation; time management; self-testing; and using academic resources. This research is a basic reference to reveal the relationship between mathematical communication skills and students’ self-regulated learning abilities. Keywords: Communication Ability, Self-Regulated Learning